Text Detection Using Image Processing: A Survey - Prasad mishra, Laxmi; Narayan Mohanty, Mihir (International Journal of Psychosocial Rehabilitation, 2025)
The aim of text recognition is to recognize the text from written hard copy documents to the required format. The process of text recognition including many steps as well as preprocessing, image segmentation, feature extraction, classification, post-processing. Preprocessing is for doing the essential operation on input image like binarization that converts gray Scale image into Binary Image, noise reduction that removes the noisy signal from an image. Segmentation process for the segment the given image into line by line and segment every character from the segmented line. Future extraction calculates the characteristics of a character. A text classification contains the information and will the comparison. Today, it plays a crucial role within the workplace, university, etc. necessary approaches wont to undergo these stages and their corresponding advantages, disadvantages, and application are presented during this article, numerous text-related applications for imagery also is presented over here. This review performs a comparative analysis of elementary processes during this field